Implementasi Undang-Undang No. 22 Tahun 1997 Tentang Narkotika - Sahal afhami sahal (Justicia Journal, 2012)
The problem in this research is how the pros and cons of the UU No. 22 of 1997 on narcotics and its implementation in the field?. In order to determine the strengths and weaknesses of Law No. 22 of 1997 on narcotics and its implementation in the field, the authors use the law narmatif sociological research methods.It was concluded that the excess of Act No. 22 of 1997 is a more complete and perfect load of Article 104 where the Act previously only contains 55 articles. Weakness of UU No. 22 Year 1997 on Narcotics, namely: lack of action in the form of socialization of UU No. 22 Year 1997 on Narcotics, lack of supporting funds for the implementation of UU No. 22 Year 1997 on narcotics, lack of mastery of the Act No. 22 1997 On Narcotics.